2005
DOI: 10.1039/b415959d
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-free synthesis of amphiphilic diblock copolymer nanoparticles via nitroxide-mediated emulsion polymerization

Abstract: Amphiphilic hairy nanoparticles are prepared in a one step, batch, heterogeneous polymerization of styrene or n-butyl acrylate, using a water-soluble poly(sodium acrylate) alkoxyamine macroinitiator based on the SG1 nitroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(193 citation statements)
references
References 10 publications
7
180
0
6
Order By: Relevance
“…When temperature was increased above the critical temperature, the copolymer chains self-assembled again into a viscous dispersion, but the particles exhibited a diameter significantly larger than the original ones, certainly because the characteristics of the copolymer chains were no longer the same as when particles initially formed during the polymerization step. [13] At low T and low pH, they formed ''inverse'' particles with a hydrophobic PAA core and a hydrophilic PDEAAm shell, whereas precipitation occurred at low pH and high T (see Figure 1). Such solubility results are analogous to those reported by André et al for PAA-b-PDEAAm prepared by anionic polymerization.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When temperature was increased above the critical temperature, the copolymer chains self-assembled again into a viscous dispersion, but the particles exhibited a diameter significantly larger than the original ones, certainly because the characteristics of the copolymer chains were no longer the same as when particles initially formed during the polymerization step. [13] At low T and low pH, they formed ''inverse'' particles with a hydrophobic PAA core and a hydrophilic PDEAAm shell, whereas precipitation occurred at low pH and high T (see Figure 1). Such solubility results are analogous to those reported by André et al for PAA-b-PDEAAm prepared by anionic polymerization.…”
Section: Resultsmentioning
confidence: 96%
“…A similar route was applied in the past for the emulsion polymerization of styrene and butyl acrylate leading to the in situ formation of amphiphilic diblock copolymer nanoparticles analogous to crew-cut micelles. [13] In a first step, a short PAA block with an alkoxyamine reactive end-group was synthesized by the direct polymerization of acrylic acid in 1,4-dioxane using the nitroxide SG1 as a mediator. Synthesis of the macroinitiator and chain-end characterization have been previously described in detail.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, their sizes were varied upon a change in pH of dispersions, ranging from 65 nm for PS particles and 90 nm for PBA particles at pH ¼ 7 to 55 nm for PS and 76 nm for PBA at pH ¼ 4. 205 For RAFT emulsion polymerization, a water-soluble macroRAFT agent was prepared by RAFT polymerization of N,N-(diethylamino)ethyl methacrylate (DEAEMA) in the presence of CPDB RAFT agent in EtOH at 60 C. After purification in acetone under alkali conditions, CPDB-terminated P(DEAEMA-H þ Cl À ) with narrow M w /M n ¼ 1.3 was used as macroRAFT agents for surfactant-free batch emulsion polymerization of St at 70 C. Monomer conversion was completed within 3 h, producing a stable latex particle with a diameter of 95-112 nm. The conversion versus time plot suggested that the nucleation mechanism involves the reaction of water-soluble oligoradicals with macroRAFT agents, leading to the formation of amphiphilic block copolymers as stabilizers in batch emulsion polymerization.…”
Section: Use Of Controlled Hydrophilic Polymers For In Situ Formationmentioning
confidence: 99%
“…17 Several recent papers report successful results using a batch process with amphiphilic macro-RAFT agents formed in situ in the presence of monomer droplets. [63][64][65][66] In particular, the development of systems where the nucleation step is based on self-assembly of block copolymers [67][68][69][70][71] require no low molecular weight surfactant, as that function is fulfilled by the amphiphilic block copolymer.…”
Section: C Block Copolymer Synthesis By Clrpmentioning
confidence: 99%
“…[220][221][222] Amphiphilic block copolymers PAA-b-PSt or PAA-b-P n BuA were prepared in water using a PNaA-SG1 at 120 °C. A stable emulsion of spherical nanoparticles was obtained through PISA as the hydrophobic block grew.…”
Section: D Nmp In Emulsion/dispersionmentioning
confidence: 99%